The subtle power of spiritual abuse - Johnson, David W. (Bethany House Publishers, 1991)
Churches are meant to be safe places where spiritual leaders help and equip the members for the work of service. There are some churches, however, where leaders use their spiritual authority to control and dominate others, attempting to meet their own needs for importance, power, intimacy or spiritual gratification. Through the subtle use of the right "spiritual" words, church members are manipulated or shamed into certain behaviors or performance that ensnares in legalism, guilt and begrudging service. This is spiritual abuse, and the results can be shattering. Deeply ingrained spiritual codes of written and unwritten rules control and condemn, wounding believers' spirits and keeping them from the grace and joy of God's kingdom. Believers find themselves enslaved to a system, a leader, a standard of performance that saps true spiritual life. This is a message for Christians who feel they are spiritually abused and for those who might be causing it. Authors VanVonderen and Johnson address these important themes and point the way toward freedom: What are the abusive spiritual dynamics that can develop in a church? How do people get hooked into these abusive systems? What are the marks of false spiritual leadership and their impact on a congregation?